The Implementation of Poster Learning Media and Its Corelation between Deep Learning and Learning Outcomes on Islamic Culture and History Subject - Huwaida, Jaziela; Chasna, Aisyatuk Makarimil (Universitas Muhammadiyah Surakarta, 2025)
This study aims to determine the increase in activeness and learning outcomes by applying poster learning media in Islamic Date material. However, based on observations, the initial score of class 4F 1442-1443 reached an average of 3.10, from these data researchers concluded that learning outcomes in Islamic Tarikh subjects decreased so it needed to be improved. With this, researchers take action by applying poster learning media in increasing student activeness and learning outcomes. This research is a Classroom Action Research by Kemmis & Mc Taggart, which consists of four stages, namely, planning, action, observation and reflection, which are held in two cycles to determine student activeness and learning outcomes. To obtain the necessary data, researchers use observation, documentation and test methods. The results of research on Islamic Date subjects grade 4F at Pondok Modern Darussalam Gontor Putri Campus 2 Academic Year 1444-1445 with the following evidence: 1. In the first cycle student activity reached 51.38% of 39 students and in the second cycle student learning activity reached 75.08% of 39 students. 2. The application of poster learning media improves student learning outcomes in Islamic Date subjects, namely with the achievement of the first cycle 17 children are considered to reach an average, with a prestase of learning outcomes of 43.59% and learning outcomes in the second cycle reaching 35 children are considered to reach an average with a percentage of learning outcomes of 89.74%.